On becoming leaders: Malaysian university students, community service and service learning / Musramaini Mustapha … [et al.] - Mustapha, Musramaini; Baharum, Norzie Diana; Mohd Burhan, Norhapizah; Abdul Razak, Nor Hidayatun (2011)
It is undeniably true that the young we raise today are the reflections of the leaders that we are going to present tomorrow. Having said this, it is thus imperative to better equip the youngsters - in the context of higher learning institution, the students - with valuable skills required to achieve a promising future. In a higher learning centre, producing leaders for, and of the nation might take different forms. Immersing the students in community services, service learning and acts of volunteerism is one of the common designs for leadership growth in many universities all around the world. This conceptual paper thus looks at the positive outcomes of students ' engagement in community-based activities. Besides, this paper also explains how these two community-based activities, with their numerous benefits, enhance the leadership skills of our students.